Continuous nanofluids jet impingement heat transfer and flow in a micro-channel heat sink. (November 2018) - Naphon, P.; Nakharintr, L.; Wiriyasart, S.
Highlights: Due to high-density electronic components, small scale of electronic devices, and high generated heat rate, the dissipation of the generated heat is a momentous embarrassment. Therefore, many innovative ideas have been proposed for thermal cooling enhancement in the electronic devices. The most common heat transfer enhancement technique is the miniaturized technology, mini and micro-components with jet impingement technique for the electronic devices. The numerous papers presented the study on the jet impingement heat transfer of the conventional coolant including air, water, oil and ethylene glycol mixtures. However, it is well known that the heat transfer capability is limited by the working fluid flow behaviors and thermal physical properties which results in poor heat transfer rate. However, there are many still room to discuss in the micro-channel heat sink especially effect of relevant parameters on the heat transfer enhancement of the system. Therefore, a combined three heat transfer enhancement techniques; jet impingement, nanofluids, micro-channel to the thermal performance of micro-channel heat sink are investigated which considered effect of jet-plate spacing, jet diameter, flow rate, nanofluids concentration, and heat input on the heat transfer and pressure drop of TiO2 nanofluids in the micro-channel heat sink. The obtained experimental results show that the suspending of nanoparticles in the base fluid remarkably increases the convective heat transfer in 18.56% at 0.015% nanofluids concentration. The suspending of nanoparticles bring almost no extra addition of pressure drop as comparing with the base fluid. However, the obtained results point out that the proper selection of the relevant parameters to enhancement of heat transfer is important. Abstract: Experimental investigation on the TiO2 nanofluids jet impingement heat transfer and flow characteristics in the micro-channel heat sink are carried out. In the present study, three heat transfer enhancement techniques; micro-channel heat sink, jet impingement, and nanofluids are considered in which included the effect of relevant parameters of the nanofluids concentration, nozzle diameter, nozzle-to-heat sink distances, mass flow rate of nanofluids on the heat transfer performance of a micro-channel heat sink are considered. The obtained results showed that the suspending of nanoparticles in the base fluid remarkably increases the convective heat transfer by 18.56% at 0.015% nanofluids concentration. In addition, the obtained heat transfer coefficient tends to increase with increasing the nozzle diameter and decreasing nozzle level height. While the pressure drop across the test section increases as the nozzle diameter decreases and nozzle level height increases. However, the suspending of nanoparticles bring almost no extra addition of pressure drop as comparing with the base fluid. However, the obtained results point out that the proper selection of the relevant parameters to enhancement of heat transfer is important.